(untitled) (The Shivapuri Journal, 2026)
Being small doesn’t limit Nepal’s efficiency to participate and become a number 1 contributor to UN peacekeeping. Nepal has limited hard power, but still, peacekeeping helped Nepal to be visible in international forums. Remittance and economic support from peacekeeping directly support the family and gradually contribute to the national economy and other development. Nepal’s military service abroad has a long history (e.g., the Gorkha regiment, British Army) and that has evolved as a modern form of soft power through UN peacekeeping. Nepal also became an inclusive and progressive nation by gradually increasing participation of women peacekeepers. Due to political complexity and resource limitations, peacekeepers face dangerous environments, but still Nepali peacekeepers shine as brave security forces. Peacekeeping transforms military capability into international trust, moral authority, and diplomatic credibility rather than coercive influence. This study uses qualitative research methods. The study makes use of both primary and secondary sources of data. The major finding is that UN peacekeeping remains the most visible and influential among Nepal’s various forms of soft power. It reflects both the professionalism and bravery of the Nepali Army. Limited research has been conducted before that focuses specifically on its socio-economic impact on Nepal. This study tried to fill that gap by identifying Nepal’s principal sources of soft power grounded in Joseph Nye’s theoretical framework and analyzing how peacekeeping participation enhances Nepal’s soft power projection and exploring the socio-economic effects of mission-related remittances, particularly at the household level.